2022
DOI: 10.1155/2022/8497417
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Maternal and Cytoplasmic Effects on Resistance to Zymoseptoria tritici in Durum Wheat

Abstract: Septoria tritici blotch (STB) is a major disease problem of wheat worldwide. To optimize the introgression of resistance genes in elite genotypes throughout traditional or molecular breeding programs, a full understanding of the quantitative inheritance of resistance to Zymoseptoria tritici, plant height (PH), and thousand kernel weight (TKW) is needed. In this study, maternal and cytoplasmic effects of resistance to STB were investigated using P1 (susceptible, high-yielding line) and P2 (resistant, low-yieldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Why do these two hybrids exhibit such different characteristics even though they contain the same single haplotype H5 ? A recent study indicated that maternal and cytoplasmic effects influence multiple traits in durum wheat, such as resistance to Zymoseptoria tritici , plant height, and thousand kernel weight ( Hassine et al, 2022 ). Therefore, perhaps, the haplotype H5 has maternal effects on the hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Why do these two hybrids exhibit such different characteristics even though they contain the same single haplotype H5 ? A recent study indicated that maternal and cytoplasmic effects influence multiple traits in durum wheat, such as resistance to Zymoseptoria tritici , plant height, and thousand kernel weight ( Hassine et al, 2022 ). Therefore, perhaps, the haplotype H5 has maternal effects on the hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Disease and insect susceptibility/resistance in crop plants varies with male or female parent, which is also used to assess maternal and cytoplasmic effect. The phenomenon of maternal and cytoplasmic effect has been reported in disease resistance in maize [7], rice [8], durum wheat [9], and olive [10]. Resistance to the southern corn leaf blight (Cochliobolus heterostrophus) and the yellow corn leaf blight (Mycosphaerella zeae-maydis) in maize was associated with the maternally inherited T (Texas source) of male-sterile cytoplasm [7].…”
Section: Introductionmentioning
confidence: 99%